The Effectiveness of Moringa oleifera Lam Extract Lotion in Promoting Healing of Second-Degree Burns in New Zealand White Rabbits - Pellokila, Nindy Bethinia; Damanik, Efrisca Meliyiuta Boru; Buntoro, Ika Febianti; Hutasoit, Regina Marvina (Universitas Nusa Cendana, 2025)
Abstract Background: Burns are an important health problem and are responsible for 265,000 deaths worldwide. Burn healing involves a complex set of processes that must be investigated intensively to improve outcomes, particularly healing time and scar quality. One of the plants that is often used by Indonesian people as traditional medicine is Moringa (Moringa oleifera Lam). Objective: Knowing the effectiveness of Moringa leaf extract lotion (Moringa Oleifera Lam) in accelerating the healing process of second degree burns in New Zealand White rabbits Methods: This study used a true experimental design and the post-test-only controlled group, that is, data collection was carried out after the treatment. Analysis of the test results using T-test Result: In the control group (P1) and the treatment group (P2), each consisted of 6 New Zealand White rabbits. Based on the modified Nagaoka criteria score, 6 rabbits were found in the treatment group with a score of 8 while in the control group there were 3 rabbits with a score of 5, 2 rabbits with a score of 6, and 1 with a score of 7 Conclusion: There is a significant difference between the treatment group and the control group where the p value <0.05 on the T-test Keyword : Burns;Moringa oleifera lam; New Zealand White Rabbit; lotion